The experimental basis for the effectiveness of the wound adsorbing bandage based on nanostructural graphite - N. V. Ryazantseva; G. P. Khandorin; O. L. Khasanov; G. I. Dubov; A. V. Shteinle; V. I. Mazin; L. A. Shteinle; O. Ye. Chechina; A. V. Ratkin (Бюллетень сибирской медицины)
The infectious complications of injuries and wounds are the actual problem of surgery. One of the most important tasks for today is the investigation of new remedies to prevent from the infectious process and to accelerate purifying processes from necrotic tissues in the wound and to intensify the wound regeneration. In this connection, to guarantee sorbing, antimicrobic, necrolitic and anesthetic protective actions is necessary to develop the first stage wound process bandage. As a result of the doctors’ and scientists’ team-work investigation a new dressing model for treating exuding wounds has been made. In the experiment this adsorbing bandage with the sorption level based on graphite particles (thermo broadened form of fluorinated graphite intercalated compound) has shown the high wound healing and drainage activity in treating associated gunshot bone-arterial injuries of extremities.